Translating and validating the hoarding rating scale-self report into Arabic - Nour Mohammad Hussain; Dalal Hasan AlMansouri; Muneera AlGhareeb; Yaser Mansoor Almutawa; Omaima Khaled Bucheeri; Mai Helmy; Khaled Trabelsi; Zahra Saif; Haitham Jahrami (BMC Psychology, 2023)
Abstract Background Hoarding disorder is characterized by a persistent inability to part with possessions due to a perceived need to keep them, regardless of their actual value. Arabic-speaking populations currently lack a validated tool specifically designed to assess hoarding symptoms. Objective This study aimed to translate, adapt, and validate the Hoarding Rating Scale-Self Report (HRS-SR) into the Arabic-language. Methods The study employed the gold standard approach to translation, involving forward translation by independent translators and back translation review. We conducted a cross-sectional study using an online survey completed by 500 participants from four Arabic-speaking countries. Psychometric analyses included internal consistency, test-retest reliability, convergent validity against generalized anxiety disorder (GAD-7), and confirmatory factor analysis. Results With a McDonald’s omega and Cronbach’s alpha of approximately 0.80, the Arabic translation of the HRS-SR showed acceptable test-retest reliability as well as good internal consistency. The survey also showed strong convergent validity with the 7-item survey for GAD-7. Confirmatory factor analysis supported a one-factor structure, confirming that each item measured the same construct. Conclusion The HRS-SR is a trustworthy and valid tool for evaluating hoarding symptoms in Arabic-speaking people. This survey could be helpful for both clinical and academic research. Future research should examine cultural variations in hoarding behavior in Arabic-speaking populations and validate the questionnaire in clinical populations.